A land of books ebook Dreams of young mexihcah word painters. - Tonatiuh, Duncan (2022)
Award-winning author-illustrator Duncan Tonatiuh sheds light on the significance of Aztec manuscripts and culture A 2023 Pura BelprÃ© Youth Illustration Honor Book Our world, little brother, is an amoxtlalpan, a land of books. In the jungles where the jaguar dwells, the Mayas make books. In the mountains the cloud people, the Mixtecs, make them as well. So do others in the coast and in the forests. And we the Mexica of the mighty Aztec empire, who dwell in the valley of the volcanoes, make them too. A young Aztec girl tells her little brother how their parents create beautiful painted manuscripts, or codices. She explains to him how paper is made from local plants and how the long paper is folded into a book. Her parents and others paint the codices to tell the story of their peopleâs way of life, documenting their history, science, tributes, and sacred rituals. Duncan Tonatiuhâs lyrical prose and beloved illustration style, inspired by the pre-Columbian codices, tell the story of howâcontrary to the historical narrative that European colonizers bestowed âcivilizationâ and knowledge to the Americasâthe Aztec and their neighbors in the Valley of Mexico painted books and records long before Columbus arrived, and continued doing so among their Nahua-speaking descendants for generations after the Spanish Conquest.Â From an award-winning author-illustrator,Â  A Land of Books Â pays tribute to Mesoamerican ingenuity and celebrates the universal power of books.